Four men looking out; one man holding up "4" on his fingers - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1958)
The plot of La Strada Lunga un Anno is divided into four major episodes, which correspond to the four seasons, beginning in autumn. These episodes are framed by an introduction and an epilogue which serve to identify the moral of the fable.
Keywords: Girotti, Massimo, 1918-2003; Italy -- Social conditions -- 1945-1976 -- Drama; Italy -- Social life and customs -- 1945--- Drama; Motion picture actors and actresses -- Italy; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Pampini, Silvana, 1925-; Rossi-Drago, Eleanora, 1925-2007; Sotlar, Bert, 1921-1992; Stills (motion pictures)